Fiscal incentives, competition, and investment in China - Bingyang Lv; Yongzheng Liu; Yan Li; Siying Ding (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper explores how fiscal incentives offered to local governments in China affect investment rates in their jurisdictions. Theoretically, we build a simple fiscal competition model to establish the linkage between local fiscal incentives and expenditure policy and consequently, capital movement. The key prediction of the model, borne out by data from Chinese provinces spanning 2004–2013, is that an increase in the local corporate income tax-sharing ratio, which proxies fiscal incentives offered to local governments, motivates local governments to compete for capital investment through increased public expenditures. Our results contribute to the fiscal federalism literature by showing that local fiscal incentives significantly shape policy choices and local economic performance. In addition, by exploring fiscal incentives offered to local governments, we offer a novel explanation for the unusually high investment rate in China that has been sustained over a prolonged period of time.
URN:NBN:fi:bof-201811212139
Keywords: H72; H77; O16; R53; 330